1977
DOI: 10.1254/jjp.27.267
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Blocking Effect of Burimamide and Metiamide on Positive Chronotropic and Inotropic Responses to Histamine in Isolated Dog Atrium

Abstract: Abstract-Whenhistamine was injected into the sinus node artery of isolated dog atrium perfused with arterial blood led from a carotid artery of the heparinized support dog, positive chronotropic and inotropic effects were dose-relatedly induced at a dose range of 0.1 to 100 Pg. The threshold dose for inducing these positive effects was approximately 0.3 ; eg. These positive responses to histamine were not blocked by tetrodotoxin, desmethylimipramine and alprenolol.These positive effects of histamine were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…In contrast, the positive chronotropic effect was abolished with Hl-receptor antagonist, and such is in agreement with the recent findings of Chiba (10). Thus, unlike the histamine-receptor in the guinea pig atrium, the histamine receptor in the dog atrial myocardium subserving the positive chronotropic effect is to be classified as H1-type receptor.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the positive chronotropic effect was abolished with Hl-receptor antagonist, and such is in agreement with the recent findings of Chiba (10). Thus, unlike the histamine-receptor in the guinea pig atrium, the histamine receptor in the dog atrial myocardium subserving the positive chronotropic effect is to be classified as H1-type receptor.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, in the dog heart, the histamine-induced positive effects appeaved to be mediated via histamine Hl-receptors (1). However, larger doses of histamine frequently induced sudden sinus arrest, as shown in the present study and in the previous paper (1). Thus, the sinus arrest may be also produced through histamine Hl receptors.…”
supporting
confidence: 88%
“…Previously Chiba (1) reported that histamine produced positive chronotropic and inotropic responses of the dog atrial muscle. Since these positive responses to histamine were blocked by a histamine Hl-receptor antagonist , tripelennamine or diphenhydramine, but were not influenced by a H2-receptor antagonist, burimamide or metiamide, or alprenolol, an adrenergic beta-blocking agent, these responses might be due to stimulation of H1 receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, histamine itself attenuated the tachycardia produced by stimulation of cardiac sympathet ic nerves via presynaptic mechanisms (8,14,15). Furthermore, positive chronotropic and positive inotropic effects of histamine in the isolated dog atrium were not blocked by tetrodotoxin (a blocker of nerve excitation), desmethylimipramine (an uptake blocker) and alprenolol (a beta-blocker), although desmethyl-imipramine slightly but insignifi cantly suppressed the histamine-induced positive chronotropic effect (16). Even in the present experiments, both the shortenings were never abolished by atenolol which almost completely abolished the noradrena line-induced shortening (Fig.…”
Section: Discussionmentioning
confidence: 99%